Arenaria acaulis (Caryophyllaceae), a new species from South Peru - Montesinos, Daniel Bernardo; Kool, Anneleen (Phytotaxa, 2015)
During studies on the flora of Moquegua (Southern Peru), some interesting Arenaria populations (subgen. Dicranilla, Caryophyllaceae) were found. The morphology of the plants does not resemble any other neotropical Arenaria species. The most similar species known so far is Arenaria boliviana (from Bolivia and Peru) from which it differs in having a shorter stem length, ciliate (not glabrous) short branches; ovate rather than oblong-lanceolate leaves always covered with dense, long trichomes, never glabrous; pedicels shorter than or equal to the size of the calyx (not twice as long), sepals broadly ovate (not ovate-oblong) and with glabrous surface, as well as in the petals. Hence, a new species—A. acaulis—is here described and illustrated.